Modified Microwave-assisted Solid-liquid Halex Reaction using Phosphonium Salt as Efficient and Robust Phase Transfer Catalyst - Mohite, Dhanaji M.; Chavhan, Pandurang M.; Basu, Arghya (Current Organic Chemistry, 2024)
A modified solid-liquid halex reaction was developed in the presence of a robust phase transfer catalyst under microwave conditions. A fast, mild, and practical microwave-assisted synthesis of 2,3-difluoro-5-chloropyridine 3 starting from 2,3,5-trichlorpyridine 1 and spray-dried KF in polar aprotic solvent was developed. The addition of Tetrakis (piperidino) phosphonium chloride as phase transfer catalyst A was studied under microwave irritation (450W) and increased the yield and significantly reduced the reaction time in contrast to the conventional heating procedure. The highest reaction rate was observed at 5 wt% phase transfer phosphonium salt catalyst to 2,3,5-trichloropyridine 1.
Keywords: microwave